IMPLEMENTASI PEMANFAATAN TEKNOLOGI DALAM PENDIKAN FORMAL DI PESANTREN (STUDY KASUS DI SMP MATHLAUL ULUM TAMBUKO SUMENEP) - Akmalun Najmi; Abd Fattah (As-Sulthan Journal of Education, 2025)
In this modern era, the discussion of pesantren (Islamic boarding school) education and technology has become highly interesting, as many pesantren are still not fully aware of the importance of integrating Islamic educational traditions with technological advancements. The pesantren education system emphasizes a learning approach that refers to religious materials and values. However, in reality, pesantren today have started adapting their learning systems to meet the challenges of modern education through technology. This research uses a qualitative method based on a case study. In this context, the researcher will objectively examine several aspects related to technology governance in education at Mathlaul Ulum Tambuko Junior High School in Sumenep. Based on the analysis of technology governance in its implementation at this school, the findings show that: First, technology governance enables digital processes, administrative efficiency, and the use of efficient tools. Second, it builds broader global connections for students to enrich their educational knowledge. Third, it enhances students' skills in accessing digital resources.